Makna Tradisi Hatsumoude (初詣) Menurut Kepercayaan Shinto di Jepang - Wahyuni, Dyah Arum Tri; Santoso, Budi (Vocational College of Diponegoro University, 2024)
Hatsumōde is the tradition of visiting Buddhist or Shinto shrines at the beginning of the year in Japan. The tradition lasts for three days, starting at 00:00 on January 1 and ending at 23:59 on January 3. The purpose is to pray to the gods for good luck in the coming year. The purpose of this research is to understand the meaning of each stage, the tools used, and the decorations at the shrine during Hatsumōde. This research uses descriptive qualitative method with literature data collection technique. Data were obtained from YouTube videos, journals, websites, and personal documentation, which are related to Hatsumōde. The results of this study show that there are certain stages in Hatsumōde, which begin with “misogi” and end with taking omikuji. In Hatsumōde, Japanese people use a 5 yen coin that means “good fortune”. There are also decorations at the shrine, namely shimenawa, shide, and ema.